2019
DOI: 10.1002/per.2216
|View full text |Cite
|
Sign up to set email alerts
|

On Post–Apocalyptic and Doomsday Prepping Beliefs: A New Measure, Its Correlates, and the Motivation to Prep

Abstract: Post‐apocalyptic scenarios provide the basis for popular television shows, video games, and books. These scenarios may be popular because people have their own beliefs and visions about the apocalypse and the need to prepare. The prevalence of such beliefs might also hold societal relevance and serve as a type of projective test of personality. However, there are no quantitative accounts of post‐apocalyptic or prepping beliefs. As such, we conducted seven studies (Ntotal = 1034) to do so. In Studies 1 and 2, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 81 publications
3
26
1
Order By: Relevance
“…A particular motivation to do so is to increase social welfare (Mischkowski, Thielmann, & Glöckner, 2019). In contrast, studies of motives to 'prep' for a doomsday scenario show that Honesty-Humility is associated with a competitive view of survival (Fetterman, Rutjens, Landkammer, & Wilkowski, 2019). Thus, individuals high in Honesty-Humility may refrain from stockpiling because they are willing to make sacrifices to promote social welfare.…”
Section: Coronavirus Pandemicmentioning
confidence: 99%
“…A particular motivation to do so is to increase social welfare (Mischkowski, Thielmann, & Glöckner, 2019). In contrast, studies of motives to 'prep' for a doomsday scenario show that Honesty-Humility is associated with a competitive view of survival (Fetterman, Rutjens, Landkammer, & Wilkowski, 2019). Thus, individuals high in Honesty-Humility may refrain from stockpiling because they are willing to make sacrifices to promote social welfare.…”
Section: Coronavirus Pandemicmentioning
confidence: 99%
“…The concept of "doomsday prepping" entered popular culture through a National Geographic Channel reality television series called Doomsday Preppers, which focussed on a subculture of people preparing for a post-apocalyptic world by hoarding supplies and weapons and rehearsing responses to hypothetical and often unlikely apocalyptic scenarios (Fetterman et al, 2019). Doomsday preppers in the pre-pandemic world often appeared to be extremists, performing elaborate drills in preparation for unlikely scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Doomsday preppers in the pre-pandemic world often appeared to be extremists, performing elaborate drills in preparation for unlikely scenarios. There is little research on psychological characteristics associated with pre-COVID-19 survivalist prepping however an initial study found that it was associated with personality factors such as low agreeableness, paranoia, cynicism, conspiracy mentality, conservatism, and social dominance orientation (Fetterman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations